Technical Procedures for Preparation and Administration of Platelet-Rich Plasma and Related Products: A Scoping Review - Pachito, Daniela Vianna; Bagattini, Ângela Maria; de Almeida, Adriano Marques; Mendrone-Júnior, Alfredo; Riera, Rachel (Frontiers in Cell and Developmental Biology, 2020)
Introduction: Platelet-rich plasma is widely used for different types of clinical situations, but universally standardization of procedures for its preparation is still lacking. Methods: Scoping review of comparative studies that have assessed at least two alternatives in one or more stages of preparation, storage and/or administration of PRP or its related products. A systematic search was conducted in MEDLINE, Embase, and LILACS. Two authors screened references independently. Data extraction was performed iteratively, and results were presented for each included comparison. Results: Thirty-nine studies were included after assessing full texts, focusing on the comparison of PRP to a related product, types of anticoagulants, centrifugation protocols, commercial kits, processing time, methods for activation, and application concomitantly to other substances. Only laboratory outcomes were assessed, as platelet, leukocyte and growth factor concentrations. Conclusion: Results showed great variability related to methods employed in different stages of PRP processing, which may explain the variability observed in clinical trials assessing the efficacy of PRP for different clinical situations.